Collaborative and Co-Creation Models in the Reform of Public Administration in the Education Sector - Senawi, Senawi; Kencana, Eva Putri; Pigome, Moses; Nurwendi, Bagus (Universitas Pahlawan Tuanku Tambusai, 2025)
This literature review explores the emerging roles of collaboration and co-creation in the reform of educational public administration. Traditional bureaucratic and hierarchical models of governance are increasingly being replaced by participatory frameworks that emphasize shared responsibility, stakeholder engagement, and innovation. Drawing from theories of New Public Governance, public value, and service-dominant logic, this review synthesizes findings from peer-reviewed journals, policy documents, and case studies published between 2005 and 2025. The study identifies four major themes: conceptual foundations of co-creation, stakeholder roles and participatory mechanisms, enabling conditions for collaborative innovation, and institutional barriers to implementation. Findings suggest that collaborative and co-creative models offer promising avenues for improving the legitimacy, responsiveness, and effectiveness of education systems. When supported by trust, leadership, adequate resources, and shared vision, these models foster inclusive and context-sensitive reforms. However, challenges such as bureaucratic rigidity, power imbalances, limited capacity, and cultural resistance continue to constrain implementation. The review emphasizes the need for context-specific, adaptive, and well-resourced approaches to institutionalize co-creation in education. By providing a thematic synthesis of current knowledge, this review contributes to both academic discourse and practical policymaking in public administration and education reform. It also highlights critical gaps for future research, particularly in developing and underrepresented contexts.